Konsistensi Organisasi Kita Pemuda Dalam Pengelolaan Sampah di Dusun Kidangberik Desa Kidangbang Kecamatan Wajak Kabupaten Malang - Tamara Adelia Nainggolan; Thuba Hkanifa Nurlaela Septi; Silvia Widyasari; Shazarina Safira Sofyan; Laila Lutfiatul Badriyah; Astrida Fitri Nuryani; Dano Purba (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The problem of waste is still a problem faced by people in Indonesia. The form of innovation needs to be presented as a strategy in overcoming waste problems in the community. The purpose of this research is to analyze the forms of innovation that have been carried out to overcome waste problems and see the consistency of the Kita Pemuda organization in carrying out waste management in Kidangberik Hamlet. The focus of this research is to look at the analysis of problems in waste management in Kidangberik Hamlet. This research will see how the village government, Kita Pemuda, and the community carry out their functions to overcome the waste problem in Kidangbang Village. The research method used is descriptive qualitative. The data sources used are primary and secondary data with data collection techniques through interviews, observation, and documentation. Determination of informants was carried out using purposive sampling techniques from the community, village government, and members of Kita Pemuda.